2016
DOI: 10.1051/0004-6361/201628196
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal asymmetries in the debris disk around HD 61005

Abstract: Context. Debris disks offer valuable insights into the latest stages of circumstellar disk evolution, and can possibly help us to trace the outcomes of planetary formation processes. In the age range 10 to 100 Myr, most of the gas is expected to have been removed from the system, giant planets (if any) must have already been formed, and the formation of terrestrial planets may be on-going. Pluto-sized planetesimals, and their debris released in a collisional cascade, are under their mutual gravitational influe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 98 publications
7
95
9
Order By: Relevance
“…The GPI data in particular highlight this trend, which is also clear in SPHERE data (Olofsson et al 2016). Farther out, the ansae appear as flat shoulders in the radial profiles beyond which there is a break in the profile slope.…”
Section: Disk Photometrysupporting
confidence: 56%
See 3 more Smart Citations
“…The GPI data in particular highlight this trend, which is also clear in SPHERE data (Olofsson et al 2016). Farther out, the ansae appear as flat shoulders in the radial profiles beyond which there is a break in the profile slope.…”
Section: Disk Photometrysupporting
confidence: 56%
“…HST STIS optical imaging from Schneider et al (2014) showed a more complete view of the low surface brightness "skirt" of dust stretching between the streamers south of the star, seen previously with NICMOS and ACS. Most recently, Olofsson et al (2016) presented high signal-to-noise ratio (S/N) VLT/SPHERE IRDIS H-and K-band images that further confirm the known features while also showing that the ring brightens with decreasing projected separation and the E ansa remains brighter than the W ansa in polarized intensity. That same work reported Atacama Large Millimeter/submillimeter Array (ALMA) 1.3 mm data indicatingthat the disk's large grains are confined to a ring with asemimajor axis of ∼66 au.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Studies of this system's SED that modeled the outer component with a modified blackbody (Kennedy & Wyatt 2010) or with a narrow belt (Ricarte et al 2013) found the warm component to be fairly cold (∼100-125 K) -consistent with the large value of r warm found here (36.1 au). In contrast, Olofsson et al (2016) modeled this SED with a wide outer belt plus a fainter and hotter (∼220 K) warm component. This suggests the outer belt comprises grains with a range of temperatures, which our model accounts for with a warm component placed far from the star.…”
Section: Contamination By Outer Dust?mentioning
confidence: 99%